Shād, Iqbāl : yaʻnī, Rājah-yi Rājāyāṉ Mahārājah Sar Kishan Parshād Shād . - Shād, Kishan Parshād, Sir, 1868 or 9-1939 (Silsilah-yi ma̤tbūʻāt-i Idārah-yi Adabiyāt-i Urdū, 1942)
Collection of letters of the Urdu writer Kishan Parshād Shād, 1868 or 9-1939 and Urdu poet Sir Muhammad Iqbal, 1877-1938 written to each other.